A Primeira Obra de História Natural do Brasil (1648): Uma análise Histórica e de Preservação. - Knippel, Phillipe; Gibaldi, Daniel; Sá, Magali Romero; Costa, Jane (Museologia e Patrimônio, 2025)
This article provides a technical-historical analysis of the Historia Naturalis Brasiliae (1648), written by the naturalists George Marcgrave and Guilherme Piso. The work was a milestone for natural sciences, documenting for the first time the biodiversity of colonial Brazil. The article contextualizes the scientific production during the governance of Maurício de Nassau, highlighting the impact of the exchange between European, Indigenous, and African knowledge. The conservation of the copy held by the Biblioteca de Manguinhos is also discussed, analyzing restoration and preservation processes. The integration of science and art, through Marcgrave's illustrations and the Baroque artistic style, is another key point. The text emphasizes the relevance of Historia Naturalis Brasiliae for the development of natural history and the contribution of empirical practices to the advancement of scientific knowledge.